To Determine Clinical Outcome of Platelet Rich Fibrin in Pulpotomy of Permanent Teeth in Irreversible Pulpitis - Sahito, Ashique Hussain; Khuhawar, Saleem Raza; Jokhio, Abdul Latif; Tagar, Muhammad Rafique; Shaikh, Mushtaque Ahmed; Kalwar, Mujeeb Rehman (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To determine the clinical efficacy of platelet-rich fibrin (PRF) in Pulpotomy of permanent teeth in irreversible pulpitis. Methodology: This observational study was conducted in the Department of Operative Dentistry, Liaquat University of Medical and Health Sciences, Jamshoro / Hyderabad, from January to December 2019, through the non-probability purposive sampling technique. Fifty patients were included of both genders, ranging from 18-50 years. Irreversible pulpitis was diagnosed by lingering pain on hot and cold touch with normal peri-apical status. The written consent was taken from all participants. Each patient was evaluated clinically for the presence of pain, and peri-apical radiographs were taken. A visual analog scale (VAS) measured patients' pain before and after treating pulpitis. After treatment of patients, the efficacy of PRF was evaluated by a pain scale. The results were statistically compiled by SPSS version-21 and applying the "t"-test. Results: The severity of pain was observed as; severe in 18 (36%), moderate in 28 (56%) and mild in 4 (8%) patients before starting the treatment. After 24 hours treating with PRF, 40 (80%) patients became pain-free, 1 (1%) with moderate, while the 9 (18%) patients were observed with mild pain; the results obtained were highly significant with a p-value <0.05. Conclusion: PRF is effective for treating irreversible pulpitis occurring in permanent teeth. Keywords: PRF, VAS, Permanent teeth, Pulpotomy, irreversible pulpitis.